Selected careers of Hospitallers in Bohemia in the 14th century - Jan, Libor (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2015)
The article analyses the careers and backgrounds of Hospitallers serving in the Czech Priory of the Order. The study discusses the limited character of sources regarding Hospitallers in Bohemia in the 13th century and presents in this context the careers of three members of the Order: Czech prior John of Zweretitz (Zviřetice), Prague Commander Pesslinus, who probably originated from a burgher family and John of Kladrubce who was a member of an insignificant aristocratic family near Strakonice. Secondly, the author demonstrates that members of the Czech Priory of the Order of St. John in the 14th century came mainly from three major groups including members of the powerful Markwartinger family from Northern Bohemia, members of burgher families from Prague and members of the lesser noble family from around Strakonice, who were dependent on the lords Bawor of Strakonice or on the local convent of St John.